1991
DOI: 10.1037/0022-3514.60.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and working models of self and actual others.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
146
1
13

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(175 citation statements)
references
References 69 publications
15
146
1
13
Order By: Relevance
“…Estos modelos influyen en la percepción acerca de la disponibilidad de los demás e influyen en su capacidad posterior para percibir apoyo y protección tanto de los padres como de otras personas significativas. Según estudios más recientes, dicha capacidad, aunque resistente al cambio, puede alterarse a lo largo del ciclo vital y, por lo tanto, se observa que la calidad de las relaciones entre padres-hijos durante la adolescencia es todavía una fuente importante de influencia en la percepción de los hijos de otros recursos de apoyo y protección extrafamiliares (Sarason et al, 1991;Simons, Chao, Conger y Elder, 2001).…”
Section: Discussionunclassified
“…Estos modelos influyen en la percepción acerca de la disponibilidad de los demás e influyen en su capacidad posterior para percibir apoyo y protección tanto de los padres como de otras personas significativas. Según estudios más recientes, dicha capacidad, aunque resistente al cambio, puede alterarse a lo largo del ciclo vital y, por lo tanto, se observa que la calidad de las relaciones entre padres-hijos durante la adolescencia es todavía una fuente importante de influencia en la percepción de los hijos de otros recursos de apoyo y protección extrafamiliares (Sarason et al, 1991;Simons, Chao, Conger y Elder, 2001).…”
Section: Discussionunclassified
“…Langford et al [42] point out, for example, that perceived social support leads to more accurate perceptions of normative peers [43]. Sarason and colleagues [43] propose that low-perceived social support may encourage downward social comparisons. Perceived social support further leads to the experience of relatedness to others, whereby facilitating students' intrinsic motivation [39,44].…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
“…Based on social comparison theory [40], research has shown that students' selfconcepts are highly influenced by their social environment and the social comparisons provided by this environment [41]. Langford et al [42] point out, for example, that perceived social support leads to more accurate perceptions of normative peers [43]. Sarason and colleagues [43] propose that low-perceived social support may encourage downward social comparisons.…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
“…A hatás érvényesülhet közvetlenül a biológiai tényezőkre is, de gyakrabban a viselkedéses stresszválasz mintázata a közvetítő tényező Seres és Bárdos, 2006 . A kötődésnek a társas kapcsolatokra, és a megküzdési stílusra is van hatása, ez utóbbi kettő egymással is kölcsönhatásban van Sarason et al, 1991 .…”
Section: Az Ibs éS a Zsigeri Eredetű Diszkomfortunclassified